Autonomic control of asystolic vasovagal syncope. Issue 5 (May 1996) - Jardine, D. L.; Ikram, H.; Crozier, I. G.
Abstract : A 30 year old woman with a lifelong history of severe, recurrent, vasovagal syncope became asystolic for 30 seconds after 37 minutes of 60 degrees head-up tilt. During early tilt, sympathetic activity, heart rate, left ventricular contractility, and cardiac output increased. Mean blood pressure was initially maintained. Presyncope was associated with maximal contractility and bradycardia despite sustained sympathetic activity. Subsequently, asystole occurred associated with complete withdrawal of muscle nerve sympathetic activity. In asystolic vasovagal reactions, presyncope may be triggered by increased left ventricular contractility and is associated with increased levels of parasympathetic and sympathetic activity. Asystole and peripheral vasodilatation may be caused by sudden and complete withdrawal of the increased sympathetic activity.